Inventaire et importance des degats des mouches des fruits sur quelques especes de cucurbitacees au Benin - Gnanvossou, D.; Hanna, R.; Azandémè, G.; Goergen, Georg E.; Tindo, M.; Agbaka, A. (2006)
Species composition and fruit fly infestation levels of 12 wild and cultivated cucurbits were determined in field surveys and in on-station trial in Benin. Six fruit fly species including Dacus ciliatus, D. vertebratus, D. bivittatus, D. frontalis, D. Punctatifrons and Bactrocera cucurbitae, were found infesting cucurbits during our surveys. Fruit infestations were higher on Cucurbita pepo, Cucumis sativus, C. Melo and an unknown cucurbit, while they were moderate on Momordica charantia, Citrullus lanatus (watermelon), Cucurbita moschata, M. balsamina and Coccinia grandis, and least on C. colocynthis, Cucumis terrestris, Lagenaria siceraria and Luffa cylindrica. In the on-station trial, three species – D. ciliatus, D. vertebratus, and B. cucurbitae– infested watermelon, cucumber and zucchini, while D. Bivittatus occurred only on watermelon and cucumber. Dacus punctatifrons rarely infested cucurbits, although it is known to be a major pest of cucurbits and solanaceous plants in parts of Central Africa. The Sri Lankan fruit fly Bactrocera invadens was recovered from two cucurbit fruits during our experiments and surveys.